Wastewater reuse for agriculture and aquaculture: current and future perspectives for low-income countries - Raschid-Sally, Liqa; Parkinson, J. (2004)
Exploiting the nutrient and water value in wastewater through agriculture and aquaculture may also help limit uncontained pollution that results from unregulated disposal of wastewater in surface water bodies. Treatment processes form an important part of wastewater reuse strategies, alongside other measures to protect health, but a concerted effort to promote capacity at all levels is required to enable the benefits of wastewater reuse to be realized.